Voltage stability assessment based on improved coupled single‐port method. Issue 10 (30th June 2017) - Cui, Bai; Wang, Zhaoyu
Abstract : This study proposes an improved coupled single‐port method for the assessment of voltage stability based on phasor measurement unit (PMU) data. The impedance matching condition, i.e. the condition that the local load impedance and the Thévenin equivalent impedance are equal in magnitude at the loadability limit point, has been a fundamental assumption of many existing studies on voltage stability assessment. However, it is shown in this study that the impedance matching can happen either before or after the loadability limit point in certain cases. The authors have proven that the inaccuracy of the conventional impedance matching condition is due to the time‐varying equivalent parameters of a power system. To deal with the dynamic nature of grid equivalence, they propose an innovative method to improve the conventional coupled single‐port method. In the new method, voltage magnitude‐to‐load consumption sensitivity is used to adjust the equivalent parameters calculated by the coupled single‐port method. Compared to conventional methods, the proposed method requires fewer PMU measurements and provides more accurate margin estimates. Case studies on extensive test systems validate the accuracy of the proposed method. The comparison between the conventional coupled single‐port method and the developed method is also provided to demonstrate the effectiveness of the new method.